2022
DOI: 10.1111/nph.18632
|View full text |Cite
|
Sign up to set email alerts
|

Does plant ecosystem thermoregulation occur? An extratropical assessment at different spatial and temporal scales

Abstract: Summary To what degree plant ecosystems thermoregulate their canopy temperature (Tc) is critical to assess ecosystems' metabolisms and resilience with climate change, but remains controversial, with opinions from no to moderate thermoregulation capability. With global datasets of Tc, air temperature (Ta), and other environmental and biotic variables from FLUXNET and satellites, we tested the ‘limited homeothermy’ hypothesis (indicated by Tc & Ta regression slope < 1 or Tc < Ta around midday) across global ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…Despite the strong role of the environment in determining T c , Guo et al (2023) also present evidence of significant thermoregulation by plants. First, they simulated the thermodynamics at three sites using the Breathing Earth System Simulator (BESS) and found that T c was consistently lower than soil temperatures, such that plants still exhibited thermoregulation even when T c > T air , as the canopy was cooler than objects without thermoregulation.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…Despite the strong role of the environment in determining T c , Guo et al (2023) also present evidence of significant thermoregulation by plants. First, they simulated the thermodynamics at three sites using the Breathing Earth System Simulator (BESS) and found that T c was consistently lower than soil temperatures, such that plants still exhibited thermoregulation even when T c > T air , as the canopy was cooler than objects without thermoregulation.…”
mentioning
confidence: 82%
“…However, the results of Guo et al . (2023) suggest that this may vary across ecosystem types, as forest ecosystems had higher thermoregulation capacity than savanna, shrublands, grasslands, and croplands in their dataset. Whether this translates to a response of forests warming at a slower rate than other ecosystem types in the context of climate change is an important question.…”
Section: Figmentioning
confidence: 95%
See 3 more Smart Citations